Life cycle assessment and short-term measurements of indoor environmental quality of a wooden family house - Vilčeková, Silvia; Harčárová, Katarína; Moňoková, Andrea; Krídlová Burdová, Eva (International Conference “Environmental Engineering”, 2020)
Nowadays, there is an increased trend in the construction of nearly zero energy buildings which can be also characterized as green buildings. Several studies confirm that wooden buildings fulfil these requirements. However, there is no detailed research related to the quality of the indoor environment in new wooden family houses. For this reason, this paper focuses on monitoring of the indoor environmental quality in a selected wooden family house. Shortterm measurements are aimed at investigation of physical parameters (air temperature, relative humidity, air velocity and noise) and chemical factors such as concentrations of particulate matters and CO2. At the same time, environmental impacts were also assessed for impact categories such as: global warming potential (GWP), ozone depletion potential (ODP) acidification potential (AP), eutrophication potential (EP), photochemical ozone creation potential (POCP) expressed as kilogram CO2eq, CFC11eq, SO2eq, PO4 3–eq and kilogram of C2H4eq within “Cradle to Grave” boundary by using the life cycle assessment (LCA) method. The main contribution of this study is demonstration that wooden buildings have substantial share in the reduction of environmental impacts. So far, results indicate that the design of wooden houses correspond with the increasing demands of occupants in terms of environmental, social and energy performance.
Keywords: wooden house; indoor environment; air quality; energy performance; LCA